The Future of Information Technology: An Analysis of Transaction Cost - Dirie, Abdirashid Awad (My University, 2006)
This thesis focuses on the potential future outsourcing through transaction cost Information Technology (IT). The emphasis here is the reduction of transaction costs in the use of information technology in outsourcing. We discuss the nature of Information Technology outsourcing, their possible impacts on socio-economic outcomes, and particularly the impacts of Information Technology on transaction costs. The study provides a theoretical discussion of how a reduction in transaction costs may affect the essence of contracts that are formulated, and in turn how that contract may affect the development path of the Information Technology outsourcing. We then turn on the components of transaction costs that examine the importance of the subject by presenting the main findings of various recent studies and elaborating on current research gaps that conveys a picture of the past research, the present findings and the future applications of Information Technology outsourcing. The thesis concludes with a broader and theoretical discussion of the potential impact of Information Technology of transaction costs.
Keywords: IT outsourcing; transaction costs theory; contract; fi=Tietotekniikka (KTM)|en=Computer Science|